Clinical outcomes following stereotactic radiosurgery for cerebral cavernous malformations of the basal ganglia and thalamus - Singh, Raj; Dumot, Chloe; Mantziaris, Georgios; Dayawansa, Sam; Xu, Zhiyuan; Pikis, Stylianos; Peker, Selcuk; Samanci, Yavuz; Ardor, Gokce D; Nabeel, Ahmed M; Reda, Wael A; Tawadros, Sameh R; et al. (Journal of neurosurgery, 2024)
OBJECTIVE: There are few reports of outcomes following stereotactic radiosurgery (SRS) for the management of cerebral cavernous malformations (CCMs) of the basal ganglia or thalamus. Therefore, the authors aimed to clarify these outcomes. METHODS: Centers participating in the International Radiosurgery Research Foundation were queried for CCM cases managed with SRS from October 2001 to February 2021. The primary outcome of interest was hemorrhage-free survival (HFS) with a secondary outcome of symptomatic adverse radiation events (AREs). Assessment of the association of prognostic factors with HFS was conducted via Kaplan-Meier analysis and log-rank test. Chi-square tests were conducted to assess potential factors associated with the incidence of AREs. RESULTS: Seventy-three patients were identified. The median patient age was 43.5 years (range 4.4-79.5 years). Fifty-nine (80.8%) patients had hemorrhage prior to SRS. The median treatment volume was 0.9 cm3 (range 0.07-10.1 cm3) with a median margin prescription dose (MPD) of 12 Gy (range 10-20 Gy). One-, 3-, 5-, and 10-year HFS were 93.0%, 89.9%, 89.9%, and 83.0%, respectively, with one hemorrhage-related death approximately 1 year after SRS and nearly 60% and 30% of patients having improvement or stability of symptoms, respectively. There was no correlation between lesion size or MPD and HFS. Seven (9.6%) patients experienced AREs (MPDs > 12 Gy in all cases). Lesion size > 1.0 cm3 was correlated with the incidence of an ARE (p = 0.019). Forty-two (93.3%) of 45 patients treated with an MPD ≤ 12 Gy experienced neither hemorrhage nor AREs following SRS versus 17 (60.7%) of 28 patients treated with an MPD > 12 Gy (p = 0.0006). CONCLUSIONS: SRS is a reasonable treatment strategy and confers clinical stability or improvement and hemorrhage avoidance in patients harboring CCMs of the basal ganglia or thalamus. An MPD of approximately 12 Gy is recommended for the management of CCM.
Keywords: Hemangioma, Cavernous, Central Nervous System; dítě; Aged; Adolescent; Treatment Outcome; Thalamus; thalamus; Retrospective Studies; lidé středního věku; senioři; předškolní dítě; lidé; kavernózní hemangiom centrálního nervového systému; Adult; Middle Aged; dospělí; Radiosurgery; Female; výsledek terapie; Male; ženské pohlaví; mladý dospělý; Humans; Child; mužské pohlaví; Young Adult; bazální ganglia; radiochirurgie; Basal Ganglia; Child, Preschool; mladiství; retrospektivní studie